A Novel Co‐based MOF as an Efficient Multifunctional Fluorescent Chemosensor for the Determination of Fe3+ and Cr2O72− in Aqueous Phase. Issue 30 (10th August 2022) - Shao, Juanjuan; Ni, Jianling; Chen, Weimin; Liu, Penglai; Liang, Yu; Li, Guangjun; Wen, Lili; Wang, Fangming
Abstract: A novel Co‐based metal‐organic framework, namely [Co3 (BTA)2 (5‐tbuip)2 ] n (LMOF‐1 ) (BTA=1H‐Benzotriazole, 5‐tbuip=5‐tert‐Butylisophthalic Acid), was successfully synthesized by solvothermal method using rigid benzotriazole as the main ligand and chromophore. The choice of ligands avoids the creation of interpenetrating structures in the structure and is demonstrated by single crystal X‐ray diffraction data. LMOF‐1 crystallizes in the tetragonal system, P4/n space group. LMOF‐1 is linked by BTA to form a one‐dimensional(1D) chain of metal clusters, which is then linked by 5‐tbuip to form a three‐dimensional(3D) network structure. The detection ability of LMOF‐1 for metal ions in water was evaluated. It is worth noting that LMOF‐1 has high selectivity and sensitivity for Fe 3+ and Cr2 O7 2−, and it has a lower detection limit of 2.18×10 6 M, 1.86× 10 6 M, respectively. The results show that LMOF‐1 is a promising chemical sensor for the detection of Fe 3+ and Cr2 O7 2− in aqueous solution. Abstract : A novel luminescent metal‐organic framework, [Co3 (BTA)2 (5‐tbuip)2 ]n (LMOF‐1), was successfully synthesized by solvothermal method. It is worth noting that LMOF‐1 has obvious quenching effect on Fe 3+ and Cr2 O7 2−, and their detection limits are 2.18× 10 6 M and 1.86×10 6 M, respectively.